A decade of uncertainty: Resolving the phylogenetic position of Diclinanona (Annonaceae), including taxonomic notes and a key to the species. Issue 6 (1st December 2014) - Erkens, Roy H.J.; Chatrou, Lars W.; Chaowasku, Tanawat; Westra, Lubbert Y.Th.; Maas, Jan W.; Maas, Paul J.M.
Abstract: The molecular phylogenetic placement of Diclinanona (Annonaceae) has been debated in the literature for a decade. On the basis of morphological studies the genus was thought to be related to genera now all placed in subfam. Annonoideae. This early hypothesis was supported by the first phylogenetic analyses of Annonaceae. However, more recently a placement in subfam. Malmeoideae was hypothesised based on an analysis of more plastid data, thus contradicting older but also new morphological findings and previous phylogenetic work. The current study uses newly sequenced plastid data for two species of Diclinanona to show that the earlier hypothesised placement was correct and discusses the (little) anatomical and morphological data on Diclinanona that is available in a phylogenetic framework. Furthermore, an online revision of the three species of Diclinanona is presented in order to update the taxonomic knowledge of this genus.